Lorcaserin treatment decreases body weight and reduces cardiometabolic risk factors in obese adults: A six‐month, randomized, placebo‐controlled, double‐blind clinical trial. Issue 6 (18th March 2019) - Tuccinardi, Dario; Farr, Olivia M.; Upadhyay, Jagriti; Oussaada, Sabrina M.; Mathew, Hannah; Paschou, Stavroula A.; Perakakis, Nikolaos; Koniaris, Anastasia; Kelesidis, Theodoros; Mantzoros, Christos S.
Abstract : Lorcaserin is a serotonin 2c receptor agonist that promotes weight loss while contributing to the prevention and improvement of type 2 diabetes and improvement of atherogenic lipid profiles, without higher rates of major cardiovascular events. The full spectrum of possible lorcaserin‐induced improvements in cardiometabolic health remains to be clarified. Thus, we investigated the way in which lorcaserin treatment may alter cardiovascular disease risk, either independently or through changes in body weight. We measured, for the first time, lipid particle quantification, lipid peroxidation, appetite‐regulating hormones and mRNA expression of the 5‐hydroxytryptamine 2c receptor (5‐HT2c receptor). A total of 48 obese participants were enrolled in this six‐month, randomized (1:1), placebo‐controlled, double‐blinded clinical trial. Lorcaserin treatment reduced fat mass ( P  < 0.001), the fatty liver index ( P  < 0.0001) and energy intake ( P  < 0.03) without affecting energy expenditure or lean mass. Total low‐density lipoprotein (LDL) ( P  < 0.04) and small LDL particles ( P  < 0.03) decreased, while total high‐density lipoprotein (HDL) P  < 0.02) increased and heart rate significantly decreased with lorcaserin treatment. No mRNA expression of the 5‐HT2c receptor was observed in peripheral organs. These data suggest that lorcaserin treatment for six months improves cardiometabolic health in obese individuals, acting mainly through the brain.